Individual freedom versus collective responsibility: too many rights make a wrong? - Looker,KJ; Hallett,TB (Emerg Themes Epidemiol, 2006)
: Individuals might reasonably expect the freedom to make their own decisions regarding their health. However, what happens when an individual's wishes conflict with what is in that individual's best interests? How far should an individual's rights be restricted for his or her own benefit? Similarly, what limitations should be placed on an individual's behaviour when that person's wishes go against what is good for the population in general? Here we discuss the issues that can arise when the rights of individuals conflict with individual and population benefits in relation to infectious diseases.